Performance evaluation of built-up composite beams fabricated using thin-walled hollow sections and self-compacting concrete. (25th October 2021) - Sahloddin, Yaser; Dalvand, Ahmad; Ahmadi, Masoud; Hatami, Hossein; Houshmand Khaneghahi, Mohammad
Highlights: The innovative built-up composite beam was presented. The design flowchart was developed to determine the ultimate bearing capacity. Effects of hallow sections spacing and slab depth were studied. Abstract: The present study proposes an innovative steel–concrete composite beam fabricated using self-compacting cementitious (SCC) composite, thin-walled steel plates, and hollow sections. In order to validate the performance of the proposed composite beam, the experimental investigation was conducted in terms of flexural strength, ductility, flexural stiffness, energy dissipation capability, and failure mode. Furthermore, the hallow sections spacing, slab depth, and SCC mixtures wereconsidered as design variables in order to probe into their effects on the structural performance of the proposed composite beam. The results indicated that hollow section spacing and fiber percentage had the most influence on load capacity and energy absorption of the composite beams. Further, the interaction between slab integration significantly prevented concrete crushing of failed composite beam. Moreover, the composite beam introduced in this study showed higher stiffness, ductility, and energy dissipation compared to the conventional one. Ultimately, a design flowchart was developed to determine the ultimate bearing capacity of the proposed composite beam.